2006
DOI: 10.1016/j.enzmictec.2005.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing MOW deinking: Laboratory scale studies

Abstract: The deinking of MOW is examined at laboratorial scale. The effect of deinking aids, pre-washing and mixing are studied. The operating conditions during pulp treatment affect the pulp and paper properties, interfering with the mechanism of ink removal and modifying the ink particle characteristics. Pre-washing the pulp facilitates the deinking process. Cellulolytic enzymes and deinking chemicals are comparable in terms of ink removal ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Conventional chemical deinking uses large quantities of chemicals, which require costly water treatment systems (Borchardt et al, 1997;Lee et al, 2007). In order to overcome these disadvantages, enzymatic deinking has attracted a great deal of attention due to its high efficiency and low environmental impact (Thomas, 1994;Pala et al, 2006;Bajpai and Bajpai, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Conventional chemical deinking uses large quantities of chemicals, which require costly water treatment systems (Borchardt et al, 1997;Lee et al, 2007). In order to overcome these disadvantages, enzymatic deinking has attracted a great deal of attention due to its high efficiency and low environmental impact (Thomas, 1994;Pala et al, 2006;Bajpai and Bajpai, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…5 mL of emulsion was mixed with 4 mL of 0.2 M phosphate buffer, pH 7.0 at 200 rpm and was run at 0°C to 65°C for 10 min, before the addition of 1.0 mL diluted enzyme followed by 30 min incubation. Reactions were stopped using 20 mL of 95% ethanol [5]. Heat inactivated enzyme was used as control and the fatty acids released during the incubation were immediately titrated with 50 mM NaOH.…”
Section: A Enzyme Assaysmentioning
confidence: 99%
“…Enzymatic deinking uses enzymes to enhance the removal of inks from waste paper and can be more effective and less expensive than conventional deinking chemicals. Also, it tends to avoid some problems associated with alternative treatment technologies [4], [5]. The mechanism of enzyme deinking has not been clearly define but several authors have reported that removal of oil-carrier-based inks can be facilitated by treatment with lipases and esterase [6] which can degrade vegetable oil based inks.…”
Section: Introductionmentioning
confidence: 99%
“…3 In order to overcome these disadvantages, enzymatic deinking has attracted a great deal of attention due to its high efficiency and low environmental impact. 4,5 The application of enzymes for replacing or enhancing traditional deinking chemicals has been reported, indicating that enzymatic deinking can get the same or better deinking results, with minimal impact on the physical properties of final paper products. 6,7 Industrial scale-up experiments with enzymatic deinking have been reported 8 and an enzyme enhanced deinking technology has been developed to be applied on a commercial scale.…”
Section: Introductionmentioning
confidence: 99%